A cultural training for the improvement of cognitive and affective Theory of Mind in people with Multiple Sclerosis: a pilot randomized controlled study - d’Arma, Alessia; Valle, Annalisa; Massaro, Davide; Baglio, Gisella; Isernia, Sara; Di Tella, Sonia; Rovaris, Marco; Baglio, Francesca; Marchetti, Antonella (Frontiers in Psychology, 2023)
Theory of Mind (ToM), the ability to understand and attribute mental states, could be impaired in Multiple Sclerosis (MS), a neurodegenerative disease affecting young adults. Considering that ToM is strictly connected to Quality of Life (QoL) in MS and that could enhance the social support network -which is particularly important for this population-, we aimed to design and implement a ToM rehabilitation training. To make it as much ecological as possible, we have devised a protocol enhancing ToM through stimuli from real-world (videoclips taken from cinema, literary fictions, audio voices). We test training's effect on both cognitive and affective components of ToM in a sample of 13 subjects, randomly assigned to the ToM training Group and to the Control Group. The following ToM tasks were administered: the Reading the Mind in the Eyes (RMET), the Strange Stories task, the Faux Pas Task and the False Belief First- and Second - Order Task (FB II and III order). We also administered a psycho-behavioral assessment through the Toronto Alexithymia Scale (TAS-20). Results show that our novel ToM training is useful in enhancing ToM abilities measured by the following tasks: the RMET (affective task, p=0.015) and the FB II-order task (FB, cognitive task, p=0.032). Our ToM training had also a significant effect on the total score of the TAS-20 Scale (p=0.018) and on its "Difficulty Describing Feelings subscale" (p=0.018), indicating a reduction of the alexithymia traits. Future works with larger samples could investigate the ToM training effectiveness in a more representative MS populations.